Self Service Technology, Kualitas Layanan Jasa, Pemasaran Hubungan (Relationship Marketing) terhadap Loyalitas Nasabah melalui Kepuasan Nasabah Bank BCA KCP Kupang Jaya Surabaya - Redy Eko hari Suprapto; Rossitya Dwi Setyawardani (STKIP PGRI SITUBONDO, 2023)
This study aims to determine the effect of self service technology, service quality, relationship marketings on customer loyalty through customer satisfaction. This study uses the subject of Bank BCA KCP Kupang Jaya Surabaya and data analysis using quantitative analysis with analytical techniques using path analysis. The data was obtained by purposive sampling technique and the researcher distributed questionnaires to the customers of Bank BCA KCP Kupang Jaya Surabaya and a sample of 100 respondents. The results showed that self service technology, service quality, relationship marketing had a significant direct effect on customer satisfaction, while service quality and relationship marketing had a significant effect on customer loyalty, while self service technology and customer satisfaction had no significant effect on customer loyalty. The results of the path analysis test show that customer satisfaction is not an mediasi variable in the effect of self service technology on customer loyalty, customer satisfaction is not an mediasi variable in the influence of service quality on customer loyalty and customer satisfaction is not an mediasi variable in the effect of relationship marketing (relationship marketing) on customer loyalty.